Economic Growth and Foreign Direct Investment in Africa: The Mediating Role of State Fragility and Natural Resources. - Barugahara, Florence; Munyambonera, Ezra (Kabale University, 2024)
Using data from 43 African countries from 2000-2018, the study employed the Dynamic System GMM approach to examine the moderating effect of state fragility and natural resources on the FDI–economic growth nexus. The study found that FDI does not affect Africa's economic growth directly or indirectly after interacting with FDI with state fragility and natural resources. The insignificant impact of FDI on economic growth in Africa may be because for FDI to promote economic growth, some necessary factors, such as institutional development and the state of the economy, must be developed to a certain level high enough for the effect to be experienced. Given that African countries are fragile with low levels of institutional development, the FDI growth nexus is insignificant. The study recommends that African countries establish stable economies and develop their institutions to benefit from FDI inflows.